Status Review of the Mangroves Forest in India - Jagdish Prasad, (International Journal of Scientific Research in Science and Technology, 2025)
Mangroves, are woody salt tolerant halophytes. They are highly productive economic bio-resources. The mangroves ecosystem currently represent less than 1% of the global tropical forest area. They supports a variety of organism both in coastal and marine ecosystems. They provide essential breeding grounds for many aquatic animal species, crustaceans, amphibian and mammals. They act as carbon sink that provide protection against more carbon, contamination and coastal erosion. Many genera depend on mangrove for their survival. Mangroves offers a wide range of ecosystem services and commercially valuable products. Over the past 50 years, this unique ecosystem has been threatened by a variety of natural causes and anthropogenic pressure. Natural causes of mangrove forest degradation are the changes in hydrology, natural disasters, global warming, climate change, and coral reef destruction. They face threats due to habitat loss, expansion of aquaculture, pollution, timber loss. The extinction and loss of biological diversity is another challenge in the mangrove forest. India continuously loosing mangrove area and about 40% mangrove area has disappear in the last century due to anthropogenic pressure. Therefore, it is essential to assess the status and trends of mangroves in India. The mangrove forest areas are promising, but using all these areas requires some challenges to answer.
Keywords: Mangroves; coastal; biodiversity; carbon -sink